THE PRIMARY SCHOOL TEACHERS’ AWARENESS LEVEL ABOUT PREPARATORY PART OF PHYSICAL EDUCATION CLASSES - Ahmet Međedović; Enver Međedović; Omer Špirtović (Sport Mont, 2010)
Our team explored the structure of physical education classes, ie. representation of the exercise, as well as the effective exercise time in the preparation of the classes, observed during the students’ exercise time, comparing the difference in training with and without equipment, the relationship between the total duration of the preparatory part of the class, as well as some of its specifics. We considered the role of formation exercise, its application in terms of prevention and correction, at first its action as stimulating factor at the body functioning, ie. exercises that prepare locomotion organs for complex physical activity and more effort. Research will show how teachers affect the realization of program content in the preparation of the class, their attitude and opinion, as well as the influence of teachers’ education and employment duration at the implementation of the engagement at this phase of class. We used polling, and survey instrument is constructed for the purpose of this observation. It contained twelve questions that had been directly related to the preparatory part of physical education class. The sample of research consisted of both sexes teachers and measured values were statistically processed. Results are represented at the table and responses were ranked and its values were graphicly displayed.